Measured effect of some socio-demographic factors on depression among breast cancer patients receiving chemotherapy in Lagos State University Teaching Hospital (LASUTH) (2011)
Background: Breast cancer is a disease predominantly found amongst women. It is a disease which threatens an organ that is intimately associated with a woman’s self image, sexuality, as well as her reproductive and nurturing capacity. These threats have serious psychological implications for women living with breast cancer. Objective: To examine the pattern and predictors of depressive symptoms among breast cancer patients receiving chemotherapy in the Lagos State University Teaching Hospital (LASUTH). Methods: Ethical approval was obtained for an ongoing multi-centre study. The data used in this study are pre-test scores from breast cancer patients in the Lagos State University Teaching Hospital. The 21-item Becks Depression Inventory II (BDI-II) was administered on 33 purposively sampled breast cancer patients who read and signed informed consent forms before taking part in the study. Results: Analysis of data using simple percentages showed that the 33 participants indicated varying degree of depressive symptoms: 13 (39.4%) of the respondents had minimal depression, 12 (36.4%) of them had mild depression, 3 (9.1%) had moderate depression, and 5 (15.2%) had severe depression. The average BDI-II score yielded 16.09 indicating mild depression. Multiple regression analysis results showed that being informed about breast cancer, average monthly income, cancer stage and educational level significantly predicted participants’ level of depression. Conclusion: This study confirmed the presence of depressive symptoms in cancer patients in Nigeria. It was recommended that intervention programs to help reduce these depressive symptoms be developed.